2015
DOI: 10.3372/wi.45.45209
|View full text |Cite
|
Sign up to set email alerts
|

The orchid flora of Turkish graveyards: a comprehensive field survey

Abstract: Graveyards in Turkey are widely known among orchidologists as places where several orchid (Orchidaceae) taxa can be found, including some very rare and localized ones. Graveyards are less strongly affected by landscape-altering human activities than other habitats because of their special cultural roles and religious privileges. In this study we performed a comprehensive survey of Turkish graveyards as orchid habitats. In total, 300 graveyards were studied in 30 provinces of Turkey in 2014. Altogether, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 21 publications
0
33
0
3
Order By: Relevance
“…Botanist and amateur orchid enthusiasts recognized decades ago that orchids regularly occur in Turkish graveyards (Kaya, Varol, & Aytepe, 2008;Kreutz, 1998;Kreutz & Çolak, 2009;Sundermann & Taubenheim, 1978). A comprehensive field survey of orchids in Turkish graveyards was carried out recently; this study also demonstrated that salep harvesting does occur in Turkish graveyards (Löki et al, 2015). However, the actual amount of the collected species, the number of collected individuals, and generally the collecting preferences of local people are unknown.…”
mentioning
confidence: 80%
“…Botanist and amateur orchid enthusiasts recognized decades ago that orchids regularly occur in Turkish graveyards (Kaya, Varol, & Aytepe, 2008;Kreutz, 1998;Kreutz & Çolak, 2009;Sundermann & Taubenheim, 1978). A comprehensive field survey of orchids in Turkish graveyards was carried out recently; this study also demonstrated that salep harvesting does occur in Turkish graveyards (Löki et al, 2015). However, the actual amount of the collected species, the number of collected individuals, and generally the collecting preferences of local people are unknown.…”
mentioning
confidence: 80%
“…[24]). During our work, we met local residents who revealed that they have significant knowledge related to orchids (three study locations are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In Turkey, tubers of the terrestrial orchids have been collected for centuries, and used for making a hot winter beverage (salep) and ice-cream (salepi dondurma), and are still used for those purposes [13,14]. Salep collection is considered one of the most important threats to orchids in the Balkans [15], in the Southwestern Asia [16,17], and especially in Turkey [13,[18][19][20][21][22][23][24]. Germany is one of the major importers of salep in Europe: the number of excavated, exported orchid individuals just for salep in Germany is approximately 3 or 4 million individuals per year [19].…”
Section: Introductionmentioning
confidence: 99%
“…These specific flowers play an important role in pollination by developing a particular life history strategy in response to evolutionary selective pollinator pressure (Adams and Lawson, 1993;Weston, et al, 2005). In terms of ethnobotany, in Eastern Mediterranean countries called "Levant," the dried underground tubercles of some Orchis species often used as a cooking powder by the local people in a hot beverage named "Saleb" or refreshment ice cream named "dondurma" (Kasparek and Grimm, 1999;Kreutz and Çolak, 2009;Löki, et al, 2015). However, it has been reported (Sezik, 2002;Kreutz, 2004;Löki, et al, 2015) that these tubercles collecting activity became threats to Orchidaceae family, especially subtribe Orchidinae (Ophrys, Orchis, Himantoglossum, and Anacamptis) in the Levant.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of ethnobotany, in Eastern Mediterranean countries called "Levant," the dried underground tubercles of some Orchis species often used as a cooking powder by the local people in a hot beverage named "Saleb" or refreshment ice cream named "dondurma" (Kasparek and Grimm, 1999;Kreutz and Çolak, 2009;Löki, et al, 2015). However, it has been reported (Sezik, 2002;Kreutz, 2004;Löki, et al, 2015) that these tubercles collecting activity became threats to Orchidaceae family, especially subtribe Orchidinae (Ophrys, Orchis, Himantoglossum, and Anacamptis) in the Levant. In Kurdistan Region, the local people (such as in Amadyia and Barwarya Bala) collect Orchids' tubercles and then sell the powder to Turkish traders which they in turn sell it in traditional Turkish markets (Véla, et al, 2013;Youssef, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%